Financial Technology dan Kinerja Berkelanjutan Usaha Mikro Kecil : Mediasi Literasi Keuangan dan Inklusi Keuangan - Emmelia Tan; Muh. Syahwildan (JURNAL ILMIAH MANAJEMEN & BISNIS, 2022)
Purpose -This study aims to examine the impact of Fintech on the Sustainable performance of MSEs, with mediating role of Financial Literacy and Financial InclusionMethodology -The purposive sampling technique was used to get 266 samples of MSEs' owners in the West Java province. The data were analyzed using the SEM-PLS method.Findings -This empirical study revealed that Fintech positively affects MSEs' sustainable performance with small effect size. The mediating testing confirmed an essential role to strengthen the relation within research model, with largest effect size from Financial literacy. The non-linear relationship between Fintech towards financial literacy and financial literacy towards sustainable performance in the early-stage decreases, and the subsequent stage increases positivelyOriginality/Novelty -The research framework used four types of the business model of Fintech application for MSEs and applied multiple mediations concept. The non-linear relationships in the research model were analyzed using the newest WrapPLS 7.0.Implications -Implication for MSEs, in the early stage, is crucial to scrutinize the learning process, adaptation process and manage the risk appropriately to optimize Fintech for sustainable business. The issuer company needs to provide adequate and proper information to maintain continued trust from fintech users from the beginning stage of launching the productsand services.